Chronicle of Alfonso X - Thacker, Shelby, 1956-; Escobar, José (Spanish professor) (Studies in Romance languages (Lexington, Ky.), 2015)
Alfonso X (1221--1284) reigned as king of Castile and León from 1252 until his death. Known to history as El Sabio, the Wise, or the Learned, his appreciation for science and the arts led him to sponsor a number of books on the history of Spain since its Roman settlement. Among them were the Cantigas de Santa Maria, a collection of over four hundred poems exalting his favorite patron saint, Mary, and chronicles of all the kings of Castile and León, Navarre, Aragón, and Portugal. Alfonso X died before his own life could be written. His was a reign fraught with political intrigue and double cros.